2020
DOI: 10.1021/acs.jpclett.0c01545
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Mechanical Compliance of an Organic Compound toward Flexible Crystal Lasing Media

Abstract: Recently, organic crystals with mechanical flexibility have been emerging as a hot research topic due to their great potentials in flexible optoelectronics. However, organic crystals exhibiting elastic bending or plastic bending are relatively rare. In this study, we proposed a strategy to improve the probability of crystal flexibility as well as to regulate the mechanical properties by controlling polymorphism. Three different emissive organic polymorphs Cry-G, Cry-Y, and Cry-O with elastic, plastic, and brit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 47 publications
1
54
0
Order By: Relevance
“…30 In this sense, in order to study the properties about tensile stimulus response of crystals, the key requirement is that crystals should be flexible and stretchable. Since Reddy et al first reported the elastic bending properties of organic single crystals and proposed the bending mechanism in 2012, 31 a few elastically bendable single crystals have been reported by Kahr, 32,33 Chandrasekar, 34,35 Naumov, 36,37,38 and other groups 39,40,41,42 . Recently, Hayashi and his co-workers found that the emission spectra of inner part, center and outer part of the bent 9,10dibromoanthracene single crystal were markedly different.…”
Section: Introductionmentioning
confidence: 99%
“…30 In this sense, in order to study the properties about tensile stimulus response of crystals, the key requirement is that crystals should be flexible and stretchable. Since Reddy et al first reported the elastic bending properties of organic single crystals and proposed the bending mechanism in 2012, 31 a few elastically bendable single crystals have been reported by Kahr, 32,33 Chandrasekar, 34,35 Naumov, 36,37,38 and other groups 39,40,41,42 . Recently, Hayashi and his co-workers found that the emission spectra of inner part, center and outer part of the bent 9,10dibromoanthracene single crystal were markedly different.…”
Section: Introductionmentioning
confidence: 99%
“…[25] From then on, elastic crystals exhibited good light transmission performance, laying the foundation for their applications in optical waveguide materials. [26][27][28][29][30][31][32][33][34][35][36][37][38] However, the elastic crystals with optical waveguide properties were still rare.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible organic single crystals are newly emerging crystal materials which can produce a certain degree of deformation to limited external stimulation with retaining intact macro structures, manifested as morphological bending, twisting and curling [1] . Elasticity and plasticity, two concepts from the fields of alloy and polymer science, [2] defined by whether the material recovers its original state after deformation or not, were borrowed to describe the mechanical flexibility of organic crystals [1a, 3] . Plastic and elastic organic single crystals, firstly identified in 2005 and 2012 respectively, [1h, 4] have drawn much attention of chemists and materials scientists.…”
Section: Introductionmentioning
confidence: 99%